EFISIENSI FAKTOR-FAKTOR PRODUKSI USAHA PETERNAKAN AYAM RAS PETELUR DI ASOSIASI BERKAH TELUR MAKMUR PURWOREJO - Abadi, Jaya; Zulfanita, Zulfanita; Mudawaroch, Roisu Eny (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
This study aims to determine: 1) laying hens at the Berkah Telur Makmur Association. 2) the factors that affect the production of laying hens in the Berkah Telur Makmur Association. 3) efficient use of production factors in laying hens at the Berkah Telur Makmur Association. This research uses descriptive basic method. The research location is the Berkah Telur Makmur Association of Purworejo. Determination of the research location is done by purposive sampling method. The sample in this study were 50 farmers. Sampling was done by using saturated sampling technique. Data analysis uses factors of production, feasibility and allocative efficiency. The results of data analysis show that the value of the R/C ratio is Rp. 1.35 indicates that laying hens at the Berkah Telur Makmur Association is feasible. The value of capital productivity is 35.49% higher than the prevailing interest rate, so it is feasible to operate. The average income of respondent farmer's labor productivity is Rp. 2,183,415.91/HKO is greater than the applicable labor costs so it is feasible to work. The results of data analysis showed that laying hens at the Berkah Telur Makmur Association was feasible. The factors of layers, the amount of feed, OVK, and labor had a significant effect on egg production of laying hens in the Berkah Telur Makmur Association, while the cage area factor had no significant effect. While the variable amount of feed is efficient, the variable number of layers and labor is not efficient. Variables of cage area and number of OVK are not efficient. Keywords: Layers, Feasibility, Production Factors, Allocative Efficiency